Revolutionizing Physics Education: The Impact of Advanced Educational Technologies on Learning Outcomes and Attitudes - Isroilovich, Xatamov Xumoyun; ugli, Kuchkorov Akhlidin Mirzokhid (International Journal on Orange Technologies, 2023)
The integration of advanced educational technologies has emerged as a promising approach to enhance school physics education. This article provides a comprehensive review of the impact of virtual reality simulations, interactive simulations, augmented reality applications, and computer-based modeling on students' learning outcomes and attitudes toward physics. The results from the reviewed studies demonstrate the effectiveness of these technologies in improving students' understanding of physics concepts and problem-solving skills. The immersive and interactive nature of these technologies facilitates visualization, hands-on exploration, and application of knowledge. Additionally, the integration of advanced educational technologies positively influences students' attitudes, increasing their engagement, motivation, and appreciation for physics. The pedagogical implications of these findings highlight the importance of professional development, curriculum alignment, equitable access, and collaborative learning environments. Further research is warranted to explore the long-term effects and comparative effectiveness of these technologies in school physics education. Overall, the integration of advanced educational technologies has the potential to transform physics education and create engaging and effective learning environments for students.